The influence of the interface between mica and epoxy matrix on properties of epoxy-based dielectric materials with high thermal conductivity and low dielectric loss. Issue 86 (2nd September 2016) - Mo, Hailin; Wang, Genlin; Liu, Fei; Jiang, Pingkai
Abstract : Two strategies, including in situ grafting chemicals and polymer coating micas, were used to improve the interface between mica and epoxy matrix. The epoxy composites prepared by strategy I exhibited better overall performance. Abstract : Achieving a better interface between epoxy and mica particles is the key issue to realize desirable thermal conductivity and low dielectric loss in epoxy-based dielectric materials. In this paper, we report two strategies to improve the interface between synthetic mica and epoxy resin. Polymer coated mica and organically modified mica were prepared by coating polydopamine (PDA) films and grafting a silane coupling agent (KH 560) and fluoro-chemicals via self-polymerization and in situ grafting. The thermal conductivity, dielectric loss and mechanical properties of the epoxy/functionalized mica dielectric materials were markedly improved in comparison with that of the epoxy/mica dielectric materials. The results suggests that the mechanical and dielectric properties of the epoxy/functionalized mica dielectric materials both depended on a good interface and good adhesion between mica and the epoxy matrix. The thermal conductivity of the epoxy/functionalized mica dielectric materials results from a balance of interfacial thermal resistance and quality of the interface. The better overall performance of the epoxy/mica@PDA and mica@PDA@F dielectric materials is attributed to the better interface between mica and epoxy matrix, and provided a new route for preparing epoxy-based dielectric materials with high thermal conductivity and low dielectric loss for use in electronics and the electrical industry.